Persistent organic pollutants and porphyrin levels in excreta of penguin colonies from the Antarctic Peninsula area. (19th September 2016) - Jara-Carrasco, Solange; Barra, Ricardo; Espejo, Winfred; Celis, José E.; González-Acuña, Daniel; Chiang, Gustavo; Sánchez-Hernández, Juan
ABSTRACT: Persistent organic pollutants (POPs) and their effects on Antarctic seabirds by using excreta as a non-destructive biomonitoring tool have received little consideration. Here we determine the levels of polychlorinated biphenyls (PCBs) and some organochlorine pesticides such as dichlorodiphenyltrichloroethanes (DDTs), hexachlorobencene (HCB), heptachlor, and endrin aldehyde in penguin excreta. Animal exposure to these environmental contaminants was determined through porphyrins in penguin droppings. Stool samples of Adélie penguin ( Pygoscelis adeliae ), chinstrap penguin ( Pygoscelis antarctica ) and gentoo penguin ( Pygoscelis papua ) were collected on two locations of the Antarctic Peninsula area: Base O´Higgins (Antarctic Peninsula) and Ardley Island (King George Island). Despite POPs have been banned more than three decades ago, the levels (ng g −1 ww) of PCBs (1.45-2.35), DDTs (1.33-1.76), HCB (0.51-1.70), endrin (0.48-0.71) and heptachlor (0.97-2.40) showed that these pollutants are still present in Antarctica. Porphyrin levels in excreta (4.6-6.7 nmol g −1 dw) were significantly correlated to POPs, indicating certain chemical exposure on penguin colonies that inhabit the Antarctic Peninsula area. The levels of heptachlor found in penguin guano may be affecting some biota in terrestrial sites next to nesting places. Further studies and better understanding of POPs impact on animal performance in Antarctic biota are recommended.